USULAN STPPA PENDIDIKAN ANAK USIA DINI 5 - 6 TAHUN - lilis amperawati; Durrotul Muniroh; Debie Susanti (Al Hanin, 2022)
AbstrackEarly Childhood Education is the level of education given before children enter the basic education level. This level carries out learning activities for early childhood. In this age range, children are in the golden age, which is a period where the child's brain can develop very rapidly both in physical growth and mental development. Therefore, early childhood needs to be given educational stimuli that are appropriate to their age level so that all children's potentials grow and develop optimally. There are six aspects of development that must be stimulated in order to achieve the standard of development achievement. This article attempts to describe developmental achievements for children aged 5-6 years using the study literacy method from several similar journals that have existed previously as a reference. Based on the research conducted, the stages of achievement of the growth and development of children aged 5-6 years in every aspect can be maximized by providing educational stimulation that pays attention to the principles of early childhood learning, through fun learning and playing experiences. Â Keyword: Proposal, STPPA, 5-6 years.